The Standpoint of the Intellectual Catholic Youth on Fascism and National-Socialism in Lithuania between Two World Wars - Pruskus, Valdas (Problemos, 2001)
Intellectual Catholic of young generation (such as A. Maceina, P. Dielininkaitis, F. Kemėšis, and others) perceived fascism and national-socialism as a phenomenon containing many social, political and economic ideas which caused an anxiety of the society. The young Catholics believed that the rise of this phenomenon was predetermined by the results of the World War I, which deepened the social and economic crisis as well as the crisis of democratic governance. The consequences of this crisis were mostly suffered by Italy and Germany. Exactly here the new standpoint on democracy, a state and its functioning was being formed. Trying to understand more deeply the origin and character of this phenomenon, the intellectual Catholic youth singled out two expressions of it - fascism and national-socialism. The latter (national- socialism) caused the most anxiety for them, because propagated specific conception of history. According to this conception the German (Nordic) race had to play the role of the Saviour of the Mankind. This salvation ought to be realized through a mass extermination of races of lower level, first of all, Jews. The theory of race inferiority preached by the Nazis and used by them as foundation of their activities, was antiscientific, and this was persuasively proved in the study of M. Reinys. It was also at variance with the doctrine of Catholic Church, because the state of Nazi “nationalized” the natural human rights and freedoms by assuming the right to determine the conditions and limits of a self-expression of an individual and simultaneously to dispose completely the spiritual life of the individual. So the state occupies the place of the Almighty. From the standpoint of the Christian doctrine asserting a freedom of an individual and the worth and undisposability of a person, such position was, of course, unacceptable to Catholics and was considered as a deviation guiding to a dictatorship. Intellectual Catholic youth interpreted Fascism as a political movement, aiming to establish the corporate model of state. They recognized that although the Fascist state completely subjugated an individual, depriving him of the freedoms cherished under conditions of democracy, it also committed itself to protect and ward the individual as a member of the specific corporation. They recognized that corporate management of public life considerably reduced the social tensions in fascist states, where the state put under control corporations directing them to serve for welfare of the whole state. Most important, it protected their interests within the state and abroad. The intellectual Catholic youth missed such assistance, especially to businessmen and farmers, in Lithuania governed by tautininkai, who had no clear program of social and economic development. At the same time, the youth saw an imperfection of the corporate model: a state was formed by the “top”, not taking into consideration freedom and self-determination of an individual. However, they supposed that the situation can be improved by individuals themselves. They hoped that the corporations, established in such way, in a course of time will be able to assume some functions of the state as well. So, the fascists interpreted corporations as a means to strengthen the power of the state and to extend its influence and intellectual Catholic youth considered them a way to reduce an omnipotence of the state pursuing its decentralization.
Keywords: Catholicism; fascism; National Socialism; theory of races; social and economic politics